Novel Tyrosine Kinase-Mediated Phosphorylation With Dual Specificity Plays a Key Role in the Modulation of Streptococcus pyogenes Physiology and Virulence - Kant, Sashi; Pancholi, Vijay (Frontiers in Microbiology, 2021)
Streptococcus pyogenes (Group A Streptococcus, GAS) genomes do not contain a gene encoding a typical bacterial-type tyrosine kinase (BY-kinase) but contain an orphan gene encoding protein Tyr-phosphatase (SP-PTP). Hence, the importance of Tyr-phosphorylation is underappreciated and not recognized for its role in GAS pathophysiology and pathogenesis. The fact that SP-PTP dephosphorylates Abl-tyrosine kinase-phosphorylated myelin basic-protein (MBP), and SP-STK (S. pyogenes Ser/Thr kinase) also autophosphorylates its Tyr101-residue prompted us to identify a putative tyrosine kinase and Tyr-phosphorylation in GAS. Upon a genome-wide search of kinases possessing a classical Walker motif, we identified a non-canonical tyrosine kinase M5005_Spy_1476, a ~17 kDa protein (153 aa) (SP-TyK). The purified recombinant SP-TyK autophosphorylated in the presence of ATP. In vitro and in vivo phosphoproteomic analyses revealed two key phosphorylated tyrosine residues located within the catalytic domain of SP-TyK. An isogenic mutant lacking SP-TyK derived from the M1T1 strain showed a retarded growth pattern. It displayed defective cell division and long chains with multiple parallel septa, often resulting in aggregates. Transcriptomic analysis of the mutant revealed 287 differentially expressed genes responsible for GAS pathophysiology and pathogenesis. SP-TyK also phosphorylated GAS CovR, WalR, SP-STP, and SDH/GAPDH proteins with dual specificity targeting their Tyr/Ser/Thr residues as revealed by biochemical and mass-spectrometric-based phosphoproteomic analyses. SP-TyK-phosphorylated CovR bound to PcovR efficiently. The mutant displayed sustained release of IL-6 compared to TNF-α during co-culturing with A549 lung cell lines, attenuation in mice sepsis model, and significantly reduced ability to adhere to and invade A549 lung cells and form biofilms on abiotic surfaces. SP-TyK, thus, plays a critical role in fine-tuning the regulation of key cellular functions essential for GAS pathophysiology and pathogenesis through post-translational modifications. Hence, SP-TyK may serve as a promising target for future therapeutic developments.